Rumikiru, n. gen. (Scorpiones: Bothriuridae), a new scorpion genus from the Atacama Desert - Ojanguren Affilastro, Andres Alejandro (2012)
Rumikiru, n. gen., a new bothriurid scorpion genus from the coastal Atacama Desert, Chile, is described. This is the first scorpion genus endemic to northern Chile. It is most closely related to Pachakutej Ochoa, 2004, from the inter-Andean valleys of Peru. Orobothriurus lourencoi Ojanguren-Affilastro, 2003, is transferred to the new genus and redescribed, creating Rumikiru lourencoi (Ojanguren-Affilastro, 2003), n. comb., and a second species of the genus, Rumikiru atacama, n. sp., is described.